Motivational Influence On Job Satisfaction And Its Impact On The Performance Of Agricultural Extenders In Nias District - Dachi, Adventina; Lumbanraja, Prihatin; Daulay, Pardamean (International Conference on Sciences Development and Technology, 2022)
This research aims to investigate the relationship between motivation and job satisfaction and its impact on the performance of agricultural instructors in Nias Regency. Data was collected through a survey using a questionnaire distributed to several agricultural instructors in the area. The variables studied included the instructor's motivation level, job satisfaction level, and agricultural instructor performance. The results of the data analysis show that there is a significant positive relationship between the motivation of agricultural instructors and their level of job satisfaction. The higher the level of motivation, the higher the level of job satisfaction felt by agricultural instructors. Besides that, This research also reveals that the level of job satisfaction of agricultural instructors has a positive impact on their performance in supporting agriculture in Nias Regency. The results of this research have important implications for the development of human resources in the agricultural sector. Efforts to increase the motivation of agricultural extension workers can be key to increasing their job satisfaction, which in turn will contribute to improved performance in supporting local agriculture. Therefore, it is recommended that related parties in the agricultural sector in Nias Regency pay more attention to the motivation and job satisfaction of agricultural instructors to increase the effectiveness of agricultural programs in the region. The results of this research have important implications for the development of human resources in the agricultural sector. Efforts to increase the motivation of agricultural extension workers can be key to increasing their job satisfaction, which in turn will contribute to improved performance in supporting local agriculture. Therefore, it is recommended that related parties in the agricultural sector in Nias Regency pay more attention to the motivation and job satisfaction of agricultural instructors to increase the effectiveness of agricultural programs in the region. The results of this research have important implications for the development of human resources in the agricultural sector. Efforts to increase the motivation of agricultural extension workers can be key to increasing their job satisfaction, which in turn will contribute to improved performance in supporting local agriculture. Therefore, it is recommended that related parties in the agricultural sector in Nias Regency pay more attention to the motivation and job satisfaction of agricultural instructors to increase the effectiveness of agricultural programs in the region.